Cover Feature: Atomic Layer Deposition (ALD) of Alumina over Activated Carbon Electrodes Enabling a Stable 4 V Supercapacitor Operation (4/2021). Issue 4 (1st April 2021) - Gandla, Dayakar; Song, Guanghui; Wu, Chongrui; Ein‐Eli, Yair; Tan, Daniel Q.
Abstract : The Cover Feature shows the TEM image of activated carbon surface coated with aluminum oxide using the atomic layer deposition technique. The ultra‐thin oxide coating of 5 nm or less is sufficient to stabilize the cycling performance of activated carbon based electric double layer supercapacitor under 4 V through enhanced barrier against ion diffusion in the electrolyte. More information can be found in the Communication by Dayakar Gandla et al.